Monitoring of Viral Infections in Vegetable Crops in Agroecosystems of Ukraine - Tsvigun, V.O.; Levishko, A.S.; Gumeniuk, I.I.; Mazur, S.O.; Цвігун, В.O.; Левішко, A.С.; Гуменюк, I.I.; Мазур, С.О. (PH "Akademperiodyka" of the NAS of Ukraine, 2024)
Information on the abundance and diversity of phytopathogenic viruses in Ukraine is very variable and limited. There is a high importance of a complex study of the species composition and ways of spreading crop viruses, as well as the development of epiphytotic forecasting systems, which will help to limit the ranges of these viruses and save crop yields. Consequently, the aim of our study was to explore the species composition and frequency of mono- and mixed virus infection of vegetable crops in Ukrainian agrocenoses and to identify the possible etiology of its occurrence. Methods. The samples were analyzed for the presence of viral antigens by enzyme-linked immunosorbent assay in sandwich and indirect modifications. For the detection of viral antigens in ELISA, test systems manufactured by Loewe were used. To identify the virus, the material was homogenized and purified, and then registered on a reader. Results. The frequency of vegetable crops damaged by diseases of viral etiology increased by 25–27% compared to the previous years of the study. Serological analysis showed that 59% of the studied samples of the Cucurbitaceae family and 54% of the Solanaceae family were affected by the main viral diseases most common in Ukraine. The seed way of transmission of vegetable viruses in Ukraine was demonstrated as one of the sources of viruses in agrocenoses. The presence of antigens to cucumber mosaic virus (CMV) in 14.3% of the studied seeds, zucchini yellow mosaic virus (ZYMV) – 11.2%, and tomato mosaic virus (ToMV) – 12.6% was shown. This allows us to suggest that sowing those seeds in the future will contribute to the spread of these viruses across Ukraine. Analysis of soil samples showed the presence of antigens of cucumber mosaic virus, tobacco mosaic virus, and potato virus X. The lowest level of antigens to CMV was detected in the soils of Vinnytsia region, to PVX – in the Kyiv and Cherkasy regions, and to TMV – in the Odesa region. Conclusions. Vegetable agrocenoses in Ukraine are more often affected by viruses belonging to the Tobamovirus, Cucumovirus, Potyvirus, and Tospovirus genera of the Bromoviridae, Potyviridae, and Bunyaviridae families. In addition to the increasing areas of viral monoinfection, there is an active spread of mixed infection, or "superinfection", in Ukrainian agrocenosis. Mixed infections are mainly formed during the growth and development of the tested vegetable crops. All of this leads to further significant spread of not only mono- but also mixed virus infection of vegetable crops.